CD44, Sonic Hedgehog, and Gli1 Expression Are Prognostic Biomarkers in Gastric Cancer Patients after Radical Resection. (29th December 2015) - Jian-Hui, Chen; Er-Tao, Zhai; Si-Le, Chen; Hui, Wu; Kai-Ming, Wu; Xin-Hua, Zhang; Chuang-Qi, Chen; Shi-Rong, Cai; Yu-Long, He
Abstract : Aim . CD44 and Sonic Hedgehog (Shh) signaling are important for gastric cancer (GC). However, the clinical impact, survival, and recurrence outcome of CD44, Shh, and Gli1 expressions in GC patients following radical resection have not been elucidated. Patients and Methods . CD44, Shh, and Gli1 protein levels were quantified by immunohistochemistry (IHC). The association between CD44, Shh, and Gli1 expression and clinicopathological features or prognosis of GC patients was determined. The biomarker risk score was calculated by the IHC staining score of CD44, Shh, and Gli1 protein. Results . The IHC positive staining of CD44, Shh, and Gli1 proteins was correlated with larger tumour size, worse gross type and histological type, and advanced TNM stage, which also predicted shorter overall survival (OS) and disease-free survival (DFS) after radical resection. Multivariate analysis indicated the Gli1 protein and Gli1, CD44 proteins were predictive biomarkers for OS and DFS, respectively. If biomarker risk score was taken into analysis, it was the independent prognostic factor for OS and DFS. Conclusions . CD44 and Shh signaling are important biomarkers for tumour aggressiveness, survival, and recurrence in GC.